Improving resistive switching characteristics of polyimide-based volatile memory devices by introducing triphenylamine branched structures. (April 2019) - Tian, Ye; Song, Ying; Yao, Hongyan; Yu, Huaxuan; Tan, Haiwei; Song, Ningning; Shi, Kaixiang; Zhang, Bo; Zhu, Shiyang; Guan, Shaowei
Abstract: Two novel solution-processable polyimide (PI-6FDA) and co-polyimide (CoPI-6FDA), with triphenylamine (TPA)-derived structure as electron donor units and trifluoromethyl-containing phthalimide as electron acceptor units, were designed and synthesized for polymer memory device application. The TPA branched structure was introduced into the CoPI-6FDA to modify the performance of the polymer memory devices. Compared with PI-6FDA, CoPI-6FDA based memory devices exhibit better memory performance in lower threshold voltage of −3.1 V, higher ON/OFF current ratios of 10 5, and better operation stability and charge transfer complex stability. The effect of TPA branched structures on memory performance has been further explored by optoelectronic measurements and theoretical calculation. Moreover, the optical and electrochemical measurements reveal the charge transfer mechanism of the CoPI-6FDA and PI-6FDA, which is related to the electrical bistability. The introduction of TPA branched structures was proved as a suitable strategy to fabricate the polymer memory devices with high performance. Graphical abstract: Two novel solution-processable polyimides (PI-6FDA and CoPI-6FDA) were designed and synthesized for polymer memory device application. Compared with PI-6FDA, CoPI-6FDA based memory devices exhibit better memory performance in lower threshold voltage of −3.1 V, higher ON/OFF current ratios of 10 5, and better operation stability and charge transfer complex stability. Highlights: Two novel polyimides (PI-6FDA, CoPI-6FDA) were designed and synthesized. The electronic behavior of MPPAB can tune memory behaviors from DRAM to SRAM. The TPA branched structure optimizes the memory performance. The switching performances of PI-6FDA and CoPI-6FDA depend on charge transfer.